Enhancing Marketing for Small and Medium Enterprises Using Digital Marketplaces to Address Competition - Siewe Hant Sieo (Akademi Sertifikasi Profesi Internasional, 2024)
Micro, small, and medium enterprises (MSMEs) contribute significantly to community economic resilience and employment absorption. The challenges encountered include insufficient creativity and inadequate utilization of technology. Furthermore, marketing operations are conducted traditionally, and branding techniques are suboptimal. This community program aims to assist MSMEs in Padukuhan Jowah in formulating marketing strategies by leveraging digitalization through the establishment of Google Maps accounts and the optimization of social media platforms (Facebook, Instagram, and WhatsApp). The techniques employed in this service are observation, interviewing, and implementation. We facilitate partner engagement by providing guidance on the advantages of social media. The execution of the activity proceeded seamlessly, with all participants providing favorable feedback. We execute data acquisition on Google Maps accounts and social media for micro, small, and medium enterprises (MSMEs). Economic digitalization is considered more successful in enhancing the turnover of community MSMEs and supplying supplementary information and knowledge for the development of marketing strategies.